Prevalence of cardiovascular risk factors and disease in patients with schizophrenia: baseline results from a prospective cohort study with long-term clinical follow-up - Christoffer Polcwiartek; Svend Eggert Jensen; Jens Brøndum Frøkjær; René Ernst Nielsen (Schizophrenia)
Abstract Patients with schizophrenia have excess cardiovascular risk, contributing to a reduced life expectancy of 15–20 years compared with the general population. To improve the understanding of the development and clinical trajectory of cardiovascular disease in patients with schizophrenia, we are conducting a prospective cohort study with comprehensive cardiovascular and psychiatric follow-up examinations every third year from baseline. In the present study, we aimed to describe and analyze the baseline results of this prospective cohort. The prospective cohort study enrolled participants with recent-onset schizophrenia (planned: n = 100), chronic schizophrenia (planned: n = 200), and controls for recent-onset patients (planned: n = 100) in the North Denmark Region from 2015–2019. We included 70 patients with recent-onset schizophrenia (mean age, 24.5 years; males, 54%; mean illness duration, 1 year), 165 patients with chronic schizophrenia (mean age, 49.5 years; males, 57%; mean illness duration, 21.1 years), and 85 controls for recent-onset patients (mean age, 24.4 years; males, 53%). At baseline, cardiovascular risk factors were highly prevalent in patients with schizophrenia (metabolic syndrome: 60%, hypercholesterolemia: 13%, diabetes: 13%, hypertension: 4%). Conversely, the prevalence of manifest cardiac disease, including heart failure, coronary artery disease, and atrial fibrillation/flutter was overall low (~1%). In conclusion, point-prevalences of cardiovascular risk factors were relatively high in patients with schizophrenia, while severe cardiac disease was less pronounced at baseline. Further prospective assessment is planned to determine and understand cardiovascular disease progression, and whether there are differences in the clinical trajectory between patients with recent-onset/chronic schizophrenia and controls over time.